2021
DOI: 10.1109/access.2021.3100363
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of the Site Diversity Technique in Tropical Region: Evaluation of Prediction Models Using Site Diversity Gain of Greece and India

Abstract: my).⁞ABSTRACT The satellite signal deteriorates as it propagates from the source to the ground antenna on the surface of the earth. While some losses involving the amplitude and energy of the signal are unavoidably recovered due to the long slant path through the atmosphere, the impairment due to precipitation, especially rain, can be mitigated. Site diversity is one of the ways to obtain a less rain-attenuated signal, simply by preparing the other site to receive a link similar to that of the main site. Dual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…ST, on the other hand, is a mild shower that lasts longer and is more widespread. Storm-wind rain is a rainstorm characterized by intense clouds and severe aftereffects in some local locations for brief periods [77,78]. Hence, since all the rain types are defined within the distance domain called rain cells, any two links located at different places (or cells) will experience different levels of attenuation while receiving signals from the same source [79].…”
Section: Survey Across Regionsmentioning
confidence: 99%
“…ST, on the other hand, is a mild shower that lasts longer and is more widespread. Storm-wind rain is a rainstorm characterized by intense clouds and severe aftereffects in some local locations for brief periods [77,78]. Hence, since all the rain types are defined within the distance domain called rain cells, any two links located at different places (or cells) will experience different levels of attenuation while receiving signals from the same source [79].…”
Section: Survey Across Regionsmentioning
confidence: 99%
“…As the rain-induced attenuation is getting worse, the least-attenuated signal from the diverse site would be routed to the host and used in the operation. Therefore, the backup site should be selected properly, which gives many benefits to the host [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Receiver-based diversity combining is a well-known technique which has been deeply studied, maturely developed, and widely applied in different mobile communication systems. For example, a site-based diversity was overviewed in [11] as an effective scheme to mitigate rain attenuation effects on satellites signals at tropical climates, a cluster diversity combining was suggested to accelerate the delivery of indoor autonomous vehicles' emergency alerts with less required rebroadcasts according to [12], a single-input multiple-output (SIMO) structure was presented to combine two downlinks from two receiving nodes by a Maximal Ratio Combiner (MRC) as a part of the study presented in [13] to improve the performance of a nonorthogonal multiple access (NOMA) network, the deep fading consequences inside tunnels were suppressed by utilizing multiple properly spaced antennas in a diversity scheme as confirmed in [14], MRC was deployed to enhance the performance by combining faded signals received by spatially distributed cellular base stations as depicted in [15], and the study conducted in [16] concluded that increasing transmit and receive antennas improved the performance in high-mobility communication systems even when rapidly switching channels.…”
Section: Introductionmentioning
confidence: 99%